1995
DOI: 10.1126/science.7892608
|View full text |Cite
|
Sign up to set email alerts
|

Role of Steroidogenic Acute Regulatory Protein in Adrenal and Gonadal Steroidogenesis

Abstract: Congenital lipoid adrenal hyperplasia is an autosomal recessive disorder that is characterized by impaired synthesis of all adrenal and gonadal steroid hormones. In three unrelated individuals with this disorder, steroidogenic acute regulatory protein, which enhances the mitochondrial conversion of cholesterol into pregnenolone, was mutated and nonfunctional, providing genetic evidence that this protein is indispensable normal adrenal and gonadal steroidogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
572
0
7

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 947 publications
(592 citation statements)
references
References 16 publications
13
572
0
7
Order By: Relevance
“…However, if the mutated residues are not conserved between these proteins, steroidogenic activity is retained. The findings on the new mutations in the present study are consonant with the recent genetic analysis of congenital lipoid adrenal hyperplasia (3,4,10,15). Mutations that truncate the C terminus of StAR destroy the functional activity of StAR, and all known mutations that cause amino acid replacements that inactivate the protein are clustered in exons 5-7, which encode the StAR C terminus.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, if the mutated residues are not conserved between these proteins, steroidogenic activity is retained. The findings on the new mutations in the present study are consonant with the recent genetic analysis of congenital lipoid adrenal hyperplasia (3,4,10,15). Mutations that truncate the C terminus of StAR destroy the functional activity of StAR, and all known mutations that cause amino acid replacements that inactivate the protein are clustered in exons 5-7, which encode the StAR C terminus.…”
Section: Discussionsupporting
confidence: 62%
“…COS-1 cells were transfected with the plasmid expressing the cholesterol sidechain cleavage enzyme and the plasmids expressing MLN64, MLN64 mutants, human wild-type StAR or StAR mutants, or the empty vectors by using Lipofectamine as previously described (3,4,6). Cultures were incubated in the absence or presence of ͑22R͒-22-hydroxycholesterol (5 g͞ml) for 36 h. Pregnenolone production was determined by radioimmunoassay using an antibody kindly provided by Charles Strott (National Institutes of Health) (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, defects in P450scc, adrenodoxin, and adrenodoxin reductase were eliminated by molecular genetic analysis of affected patients (5)(6)(7). Recently, the gene for steroidogenic acute regulatory protein (StAR), which functions as a labile protein factor in steroidogenesis mediating cholesterol transport within mitochondria, was cloned (8)(9)(10). Mutations in the StAR gene were subsequently identified as the cause of lipoid CAH (8,11).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, strong evidence for the key role of StAR protein in the intramitochondrial cholesterol translocation has been provided by studies on patients with lipoid congenital adrenal hyperplasia, a genetic disease which results in a complete inability to synthesize steroids. Lin and co-workers have demonstrated that this lethal condition is caused by nonsense mutations in the gene for StAR which generate truncated and non-functional proteins (9). However, the molecular mechanism whereby StAR is able to effect the intramitochondrial cholesterol transfer still remains unknown.…”
Section: Vol 45 No 1 1998mentioning
confidence: 99%